MUX/DEMUX SiC receiver for visible light communications - Vieira, Manuela (2020)
In this paper we present a MUX/DEMUX device based on a multilayer a-SiC:H optical ﬁlter that requires near-ultraviolet steady state optical switches to select desired wavelengths in the visible range. The selector ﬁlter is realized by using a two terminal double pi’n/pin a-SiC:H photodetector. Five visible communication channels are transmitted together, each one with a speciﬁc bit sequence. The combined optical signal is analyzed by reading out the photocurrent, under near-UV front steady state background. Data shows that 25 current levels are detected and corresponds to the thirty-two on/off possible states. The proximity of the magnitude of consecutive levels causes occasional errors in the decoded information. To minimize the errors, four parity bit are generated and stored along with the data word. The parity of the word is checked after reading the word to detect and correct the transmitted data. Results showed that the background works as a selector in the visible range, shifting the sensor sensitivity and together with the parity check bits allows the identiﬁcation and decoding of the different input channels. A transmission capability of 60 kbps using the generated codeword was achieved.